Efforts To Improve The Quality Of Islamic Religious Education And Thoughts Through The Jigsaw Method In Namira Junior High School Probolinggo City - Agustin, Maulid (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Efforts to improve the learning quality of Class VII Junior High School Students in Islamic Religious Education Subjects with the Jigsaw Type Learning Model at Namira Middle School in Probolinggo City for the 2021/2022 Academic Year. This research is a classroom action research that aims to improve the learning quality of students of SMP Namira City Probolinggo class VII-A with a jigsaw type of learning model. The subjects of this study were students of class VII-A SMP Namira Probolinggo City as many as 22 students. The information collection tool used is in the form of observation sheets and ordinary multiple preference objective tests, based on the results of observations in cycle I and cycle II activities, there is an increase in the quality of student learning. Universally obtained 50% of students in the first cycle and 90, 90% in the second cycle. This increase in learning quality took place because each student discussed the division of his group members into expert groups based on the teacher's direction, as well as in the group from which the students were eager to present the results of the discussion. Next, it was found that the increase in learning outcomes that appeared in the gain index criteria for each student were 11 moderate students and 11 high students in the first cycle, 20 high students in the second cycle.